1,2,4-triazole derivatives in medicine and pharmacy and application prospects - Sameliuk, Y.; Kaplaushenko, T.; Al Zedan, F.; Самелюк, Юрій Геннадійович (My University, 2021)
Development of methods for the synthesis, studies of chemical, physico-chemical and biological properties of 1,2,4-triazole derivatives, in particular compounds with heterocyclic scaffolds and complex compounds as potential biologically active substances. Result and Discussion: In this review, 40 scientific papers reporting the properties of 1,2,4-triazole derivatives were evaluated. Each class of compounds described in the review was reported with the prospect of forming the direction for further research.Because of there is no enough studies about biological action of 1,2,4-triazole derivatives in human, it encourages further research.
Keywords: Biological activity; bibliosemantic method; organic synthesis; 1,2,4-triazole